2018
DOI: 10.12659/msm.911640
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Epidermal Growth Factor Receptor (EGFR) and HER-2 in Bladder Carcinoma and Its Association with Patients’ Clinical Features

Abstract: BackgroundThe aim of this study was to determine the expression of EGFR/HER-2 and investigate their association with patients’ clinical features in bladder transitional cell carcinoma (BTCC).Material/MethodsImmunohistochemistry was utilized in our study to explore the expression of EGFR/HER-2 of 56 human bladder cancer samples and 10 normal bladder samples.ResultsEGFR and HER-2 expressions were both significantly higher in bladder transitional cell carcinoma (BTCC) than that in non-cancer bladder samples; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
(45 reference statements)
5
19
0
Order By: Relevance
“…Five of those had significant z-scores (zscore = 2.54-4.65, equivalent to p < 0.01), and the remainder had z-scores surpassing standard measures of significance (z-score-= 1.70-2.49, equivalent to p < 0.05). HER2, the gene product of ERBB2 is upregulated in 37% of human iUCs and, combined with EGFR, is associated with advanced disease stage at diagnosis and increased risk of recurrence [55]. HER2 overexpression has been identified by immunohistochemistry in 57% of canine iUCs [56] and is predicted to be an upstream regulator of gene expression in canine iUCs [28].…”
Section: Discussionmentioning
confidence: 99%
“…Five of those had significant z-scores (zscore = 2.54-4.65, equivalent to p < 0.01), and the remainder had z-scores surpassing standard measures of significance (z-score-= 1.70-2.49, equivalent to p < 0.05). HER2, the gene product of ERBB2 is upregulated in 37% of human iUCs and, combined with EGFR, is associated with advanced disease stage at diagnosis and increased risk of recurrence [55]. HER2 overexpression has been identified by immunohistochemistry in 57% of canine iUCs [56] and is predicted to be an upstream regulator of gene expression in canine iUCs [28].…”
Section: Discussionmentioning
confidence: 99%
“…The RTKs EGFR and ERBB2, when altered, are known oncogenic drivers in NSCLC and mammary tumours, as well as other carcinomas. Previous studies indicate EGFR and ERBB2 may be overexpressed in upwards of 50% and 30% of UC, respectively, and overexpression is associated with recurrent disease . Unsurprisingly, EGFR expression is not linked to well‐characterized activating kinase mutations, suggesting expression alone is insufficient in predicting a patient’s response to EGFR TKI .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced tumor grade and stage, and tumor relapse had significant increased expression of EGFR in comparison with patients with lower grade and stage of tumor, and lack of recurrence. Patients with advance stages and tumor relapse also showed increased levels of HER2 expression compared with recurrence free patients with lower tumor stages [70]. It has been shown that the EGFR up regulation and ErbB4 down regulation were significantly correlated with tumor aggressiveness, advance grade, and poor overall survival in a sub population of BCa patients.…”
Section: Rtk Class Imentioning
confidence: 95%
“… LI [ 67 ] 2015 HER2, EGFR, VEGFR USA 16 patients EGFR up regulation RAJJAYABUN [ 63 , 68 ] 2005 EGFR, HER2 UK 58 patients HER2 and EGFR up regulations IMAI [ 69 ] 1995 EGFR, HER2 Japan 30 patients HER2 and EGFR up regulations were correlated with recurrence. LI [ 70 ] 2018 EGFR, HER2 China 56 patients 10 controls HER2 and EGFR expressions were correlated with stage. KASSOUF [ 71 ] 2008 EGFR, HER2, ErbB-3, ErbB-4 Canada 248 tumors EGFR and ErbB-4 expressions were correlated with grade and survival.…”
Section: Introductionmentioning
confidence: 99%